2013
DOI: 10.1186/1471-230x-13-104
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of Helicobacter pylori infection in Korea: Nationwide multicenter study over 13 years

Abstract: BackgroundThe aim of this study was to evaluate the time trend of seropositivity of Helicobacter pylori (H. pylori) over the period of 13 years in an asymptomatic Korean population, and investigate associated risk factors.MethodsThis cross-sectional nationwide multicentre study surveyed anti-H. pylori IgG antibodies in 19,272 health check-up subjects (aged [greater than and equal to]16 years) in 2011. Risk factors for H. pylori infection were investigated using logistic regression. Seropositivity in asymptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
171
3
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 208 publications
(205 citation statements)
references
References 25 publications
20
171
3
6
Order By: Relevance
“…We found that the capital region (Seoul and Gyeonggi) showed lower H. pylori seropositivity than other areas. This trend was also reported in a previous Korean study in 2011 9. Interestingly, as the distance from the capital region increased, so did the odds ratio of H. pylori prevalence.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…We found that the capital region (Seoul and Gyeonggi) showed lower H. pylori seropositivity than other areas. This trend was also reported in a previous Korean study in 2011 9. Interestingly, as the distance from the capital region increased, so did the odds ratio of H. pylori prevalence.…”
Section: Discussionsupporting
confidence: 86%
“…Comparison of Helicobacter pylori seropositivity with previous data 7, 8, 9 in asymptomatic adult participants in South Korea…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations